INVESTMENT OPPORTUNITY SET AND CAPITAL STRUCTURE ON STOCK RETURN WITH PROFITABILITY AS THE CONTROL VARIABLE: AN EVIDENCE OF BANK COMPANIES IN INFOBANK15 - Michelle Sabatamia Pardosi; Francis M. Hutabarat (Jurnal Akuntansi, 2020)
The purpose of this study aimed to look at the effect of the Investment Opportunity Set and Capital Structure on Stock Return with Profitability as the control variable at bank companies that are listed in INFOBANK15. The sampling is used is purposive sampling. The sample that are collected is from 8 out of 15 bank companies listed in INFOBANK15 from year 2014-2018. Analysis data is done using the descriptive statistic, correlation, significant test, and linier regression analysis. Investment Opportunity Set using the CAPBVA proxy and Capital Structure using the Debt to Equity Ratio with Profitability as the variable control using the Return on Asset ratio. The result shows that Investment Opportunity Set, Capital Structure and Return on Asset have a significant effect on Stock Return. This shows that the performance of the company can have an effect on investment decisions on investors in the banks studied.